SYARIKAT ISLAM DALAM INTEGRITAS DUNIA PENDIDIKAN DAN KEWIRAUSAHAAN BAGI KEMANDIRIAN UMAT - Dr. Hamdan Zoelva; Mohammad Taufik m (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2018)
Syarikat Islam in the Integrity of the World Education and Entrepreneurship (economicempowerment of the ummah) For Self-Reliance The Ummah is an inseparable part sincethe beginning of Syarikat Islam up to the present. Although the world of education andentrepreneurship (the economic empowerment of the ummah) has long been part of theSyarikat Islam struggle, it is related to the Education Institution based on existing data,Muhammadiyah and Nahdatul Ulama (NU), much more developed than educationalinstitutions in Syarikat Islam. There are some output figures generated from education inthe broad sense of Syarikat Islam which acts as a religious figure, nation and state,including Tayeb Muhammad Gobel, Rachmat Gobel and Sandiaga Salahuddin Uno, so asto realize entrepreneurship for the independence of people in Indonesia.